PERHITUNGAN INTENSITAS GEMPA BUMI BERDASARKAN NILAI PGA (PEAK GROUND ACCELERATION) MENGGUNAKAN DATA GEMPA BUMI MULTI-EVENT (STUDI KASUS: KABUPATEN PANDEGLANG, BANTEN) - Hariyanto, Teguh; Bioresita, Filsa; Safitri, Chomia Nilam (Geoid, 2020)
Pandeglang Regency is located in the southern coast of Java Island which is adjacent to the megathrust subduction zone. This zone originates from the meeting of the Indo-Australian Plate which is subducted under the Eurasian Plate. So that it can cause frequent earthquakes due to the movement of the plunging plates. Other than that, Pandeglang Regency is also bordered by the Sunda Strait in the western part where the region has Mount Krakatau which has the potential to cause earthquakes due to volcanic eruptions. For this reason, an analysis of the calculation of earthquake intensity in Pandeglang Regency is needed as an initial step in disaster mitigation. This process uses multi-event earthquake data in the period of 2010 - 2018 and using the earthquake intensity calculation method which is calculated based on the PGA (Peak Ground Acceleration). The range of earthquake intensity in Pandeglang Regency is V - VII MMI with the largest percentage (91.463%) is VI MMI with area of 2513,526 km 2 . While the smallest percentage (0.301%) is V MMI with area of 8.27 km 2 . Districts in Pandeglang Regency which have the highest intensity of earthquakes are Angsana, Cibitung, Cimanggu, Pagelaran, Panimbang, Patia, Sindangresmi, Sobang, and Sukaresmi Districts.